Risiko sistematis dan pengembalian saham sektor kesehatan pasca pencabutan PPKM - Budiman, Sania Revalina; Tiwang, Novan Nicodemus Kodoati (Yayasan Widyantara Nawasena Raharja, 2024)
The revocation of PPKM in Indonesia on December 30 2022 has a positive impact on the country's economy. This study aims to examine the market response to policies when revoking PPKM, especially for stocks in the health sector. Observations were carried out from December 2022 to January 2023 or the period before and after the revocation of PPKM with stocks from the health sector as samples. Hypothesis testing from this study uses several procedures, namely normality tests, descriptive statistics, and difference tests. This study finds that health sector stocks experienced an increase in returns and systematic risk after the lifting of PPKM. However, this study also finds that the increase in the rate of return and systematic risk did not differ from the period before the lifting of PPKM. This finding implies that the repeal of the PPKM policy did not have a significant impact, especially on stocks from the health sector.